Preparation process of high ceramic phase gradient coating
By employing laser texturing, specific coating material formulations, and plasma spraying processes, combined with thermal shock strengthening treatment, the problems of insufficient bonding strength and thermal shock resistance of ceramic coatings have been solved, resulting in high-performance ceramic phase gradient coatings.
Patent Information
- Application Number
- CN202511145586.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-10-21
AI Technical Summary
Existing ceramic coatings are deficient in terms of bonding strength, hardness, and thermal shock resistance, resulting in poor performance under load, vibration, friction, impact, and high-temperature environments, which limits their application range and lifespan.
Laser texturing technology is used to construct micro-nano rough surfaces. Combined with specific coating material formulations and plasma spraying processes, a multi-element synergistic strengthening system is formed through gradient deposition and thermal shock strengthening treatment to optimize the coating structure.
It significantly improves the bonding strength between the coating and the substrate, enhances the hardness and thermal shock resistance of the coating, and ensures stable operation under complex working conditions.
Smart Images

Figure CN120818778A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic phase coatings, in particular to a preparation process of a high ceramic phase gradient coating. Background Art
[0002] Ceramic coatings, due to their excellent properties such as high temperature resistance, abrasion resistance, and high hardness, have been widely used in a wide range of fields, including aerospace, machinery manufacturing, and energy and chemical industries. They are typically formed by applying ceramic materials to the surface of a metal substrate through a specific process, effectively improving the substrate's performance and meeting the requirements of various operating conditions.
[0003] However, existing ceramic coatings still have some shortcomings in practical applications. In terms of bonding strength, the bond between traditional coatings and metal substrates is often not strong enough, and the coating is prone to peeling, which greatly limits its scope of use and service life.
[0004] For example, in some situations where heavy loads or vibrations are required, coatings are likely to fail due to insufficient bonding strength. From a hardness perspective, existing coatings are difficult to meet the high-demand wear-resistance requirements of some wear-resistant scenarios. When faced with high-intensity friction or impact, the coatings are easily worn, affecting the normal operation of the equipment. In terms of thermal shock resistance, many ceramic coatings are prone to cracking or even flaking when subjected to repeated thermal cycles due to insufficient coating performance, making them unable to operate stably in high-temperature environments. Summary of the Invention
[0005] In response to the above problems, the present invention provides a process for preparing a high ceramic phase gradient coating.
[0006] The specific technical solution is as follows: A high ceramic phase gradient coating preparation process includes the following steps: (1) Metal substrate pretreatment: The metal substrate is processed by laser texturing technology to construct a micro-nano rough surface with Ra1μm-2μm; (2) Coating material construction: The basic slurry includes: 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and the balance is 5wt% polyvinyl alcohol solution; Gradient slurry: The alumina powder content in the base slurry is gradually increased by 1wt%-1.5wt% to obtain; the zirconia powder and rare earth content are calculated according to the following relationship, and the content of other powder components remains unchanged, wherein the alumina powder, zirconia powder, and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; wherein the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z; (3) Plasma spraying: Adjust the spraying distance to 100mm-150mm and the angle to 80°-100°, spray the base slurry along the side of the metal substrate, and then spray the gradient slurry every 40μm coating thickness. Each time the gradient slurry is sprayed, the content of alumina powder, zirconium oxide powder, and rare earth is gradually increased based on the slurry of the previous layer to achieve gradient deposition of the ceramic phase coating; After the first layer of base slurry is sprayed, sintering is carried out, and the temperature is raised to 1550℃ under vacuum at a heating rate of 5℃ / min, kept at this temperature for 30 minutes, and then cooled to room temperature before subsequent spraying. This cycle is repeated until all coatings are sprayed and sintered. Among them, the subsequent sintering heating rate remains unchanged, the heating temperature increases by 5-8℃ per layer, and the holding time remains unchanged; During the plasma spraying process, ultrasonic vibration assistance is introduced to promote the uniform spreading and refinement of the molten droplets through ultrasonic vibration; The total spray thickness of the coating is 200 μm; (4) Thermal shock strengthening treatment: After plasma spraying, perform 3-4 thermal shocks, heating at 100-120°C / min and cooling at 60-100°C / min, using thermal stress to promote the agglomeration and refinement of ceramic phase particles. Before thermal shock strengthening treatment, the coating is vacuum annealed at a temperature of 520°C-600°C for 1-2 hours to eliminate internal stress in the coating.
[0007] As a further technical solution, the laser power is set to 150W-300W and the scanning speed is set to 90mm / s-150mm / s during the laser texturing process.
[0008] As a further technical solution, the rare earths selected are yttrium oxide, lanthanum oxide and cerium oxide, and the mass ratio of the three is 5:3:2.
[0009] As a further technical solution, the ultrasonic frequency is set to 30kHz-40kHz, and the ultrasonic power is 250W-300W.
[0010] As a further technical solution, the vacuum degree of the vacuum annealing treatment is maintained at 1×10 -3 Pa-1.6×10 - 3 Pa.
[0011] As a further technical solution, during the preparation of the basic slurry, the temperature is controlled at 75°C-80°C, the dispersion time is 1-2 hours, and the dispersion speed is 550 r / min.
[0012] As a further technical solution, during plasma spraying, the spraying gas is a mixture of argon and hydrogen, and the plasma power is 450-500W; Among them, the argon flow rate in the mixed gas is 40L / min-50L / min, and the hydrogen flow rate is 5L / min-8L / min.
[0013] As a further technical solution, in the thermal shock strengthening treatment, the high-temperature residence time of each thermal shock is 10 minutes to 15 minutes, and the low-temperature residence time is 6 minutes to 8 minutes.
[0014] As a further technical solution, after the metal substrate is pretreated, the metal substrate is plasma cleaned. The plasma cleaning time is 8min-10min. Argon is used as the working gas for plasma cleaning. The gas flow rate is 20L / min-30L / min, the plasma power is 200W-300W, and the vacuum degree is maintained at 10Pa-16Pa during the cleaning process.
[0015] As a further technical solution, after the gradient coating is constructed, the coating surface is polished, and the surface roughness after polishing is Ra≤0.5μm.
[0016] The beneficial effects are: The high ceramic phase gradient coating preparation process provided by the present invention achieves significant performance improvements in many aspects through the rational coordination of various components and process optimization. In the metal substrate pretreatment stage, the present invention uses laser texturing technology to construct a micro-nano rough surface of Ra1μm-2μm, and simultaneously performs plasma cleaning. This not only increases the roughness of the substrate surface, providing more mechanical bite points for the coating, but also removes surface pollutants and oxide layers, improves the activity of the substrate surface, and thus significantly enhances the bonding strength between the coating and the substrate. Mainly, the rough surface structure forms a mechanical interlock with the coating, while the clean and highly active surface promotes the chemical bonding between the coating and the substrate. The combined effect of the two greatly improves the bonding strength.
[0017] The present invention achieves improved performance of high-ceramic phase gradient coatings through a specific coating material formulation and plasma spraying process. During the coating material construction stage, silicon carbide, boron nitride, silicon dioxide and rare earth elements are introduced to form a multi-component synergistic strengthening system. Among them, silicon carbide provides high wear resistance and thermal conductivity, boron nitride improves high-temperature lubricity, silicon dioxide promotes sintering densification, and rare earth elements refine grains to the nanoscale through a solid solution strengthening mechanism. In particular, the alumina, zirconia and rare earth content follow the nonlinear relationship z = 0.05x + 0.01y - 0.5. The three elements formulated under this relationship produce a triple synergistic effect: first, the rare earth elements form lattice distortion bands between the gradient layers, effectively absorbing thermal stress; second, the zirconia undergoes stress-induced phase transformation during the gradient change, which significantly improves the fracture toughness of the coating and greatly improves the bonding strength; third, the gradual increase of alumina and rare earth doping jointly suppress high-temperature grain coarsening, so that the coating still maintains nanostructure stability after sintering and the surface hardness is significantly improved.
[0018] The plasma spraying process further enhances the coating's performance. A gradient sintering system, with a first layer at 1550°C and a temperature increase of 5-8°C per layer, forms a metallurgical bond between layers, achieving a bond strength exceeding 80 MPa. Simultaneously, 30-40 kHz ultrasonic vibrations create a cavitation effect during droplet spreading, resulting in a more uniform particle distribution, reduced porosity, and increased hardness. This microstructural optimization, combined with the material gradient design, results in a coating with exceptional overall performance, layer by layer: significantly enhanced thermal shock resistance and significantly enhanced high-temperature stability.
[0019] Vacuum annealing prior to thermal shock strengthening eliminates internal stresses in the coating, while thermal shock strengthening utilizes thermal stresses to promote the agglomeration and refinement of ceramic particles. This elimination of internal stresses prevents cracking in the coating due to stress concentration during use, while the agglomeration and refinement of ceramic particles stabilizes the coating's microstructure, significantly improving its thermal shock resistance. This is primarily due to the release of internal stresses in the coating during vacuum annealing, while the thermal stresses generated by temperature fluctuations during the thermal shock process promote the rearrangement and agglomeration of ceramic particles, forming a finer, more uniform structure and enhancing the coating's resistance to thermal cycling.
[0020] In summary, the present invention comprehensively improves the performance of the ceramic coating in terms of bonding strength, hardness and thermal shock resistance through the coordinated coordination of various components and optimization of process steps, solves the shortcomings of the existing technology, and has important practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a process flow chart for preparing a high ceramic phase gradient coating. DETAILED DESCRIPTION
[0022] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0023] The present invention provides a process for preparing a high ceramic phase gradient coating, comprising the following steps: (1) Metal substrate pretreatment Laser texturing is used to treat the metal substrate, creating a micro-nano rough surface with an Ra of 1μm-2μm. After pretreatment, the metal substrate is plasma cleaned for 8-10 minutes using argon as the working gas at a flow rate of 20L / min-30L / min and a plasma power of 200W-300W. The vacuum level is maintained at 10Pa-16Pa during the cleaning process.
[0024] (2) Coating material construction: The basic slurry includes: 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and the balance is 5wt% polyvinyl alcohol solution; Gradient slurry: The alumina powder content in the base slurry is gradually increased by 1wt%-1.5wt% to obtain; the zirconia powder and rare earth content are calculated according to the following relationship, and the content of other powder components remains unchanged, wherein the alumina powder, zirconia powder, and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; wherein the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z; (3) Plasma spraying: Adjust the spraying distance to 100mm-150mm and the angle to 80°-100°, spray the base slurry along the side of the metal substrate, and then spray the gradient slurry every 40μm coating thickness. Each time the gradient slurry is sprayed, the content of alumina powder, zirconium oxide powder, and rare earth is gradually increased based on the slurry of the previous layer to achieve gradient deposition of the ceramic phase coating; After the first layer of base slurry is sprayed, sintering is carried out, and the temperature is raised to 1550℃ under vacuum at a heating rate of 5℃ / min, kept at this temperature for 30 minutes, and then cooled to room temperature before subsequent spraying. This cycle is repeated until all coatings are sprayed and sintered. Among them, the subsequent sintering heating rate remains unchanged, the heating temperature increases by 5-8℃ per layer, and the holding time remains unchanged; During the plasma spraying process, ultrasonic vibration assistance is introduced to promote the uniform spreading and refinement of the molten droplets through ultrasonic vibration; The total spray thickness of the coating is 200 μm; During plasma spraying, the spraying gas is a mixture of argon and hydrogen, and the plasma power is 450-500W; among them, the argon flow rate in the mixed gas is 40L / min-50L / min, and the hydrogen flow rate is 5L / min-8L / min.
[0025] (4) Thermal shock strengthening treatment After plasma spraying, 3-4 thermal shocks are applied, with the temperature increasing at 100°C / min-120°C / min and cooling at 60°C / min-100°C / min, using thermal stress to promote the agglomeration and refinement of ceramic phase particles. Before thermal shock strengthening treatment, the coating is vacuum annealed at a temperature of 520°C-600°C for 1-2 hours to eliminate internal stress in the coating. The vacuum degree of the vacuum annealing treatment is maintained at 1×10-3Pa-1.6×10-3Pa. After the gradient coating is constructed, the coating surface is polished, and the surface roughness after polishing is Ra≤0.5μm.
[0026] The following are specific embodiments Example 1 (1) Metal substrate pretreatment: Laser texturing technology was used to treat the metal substrate. The laser power was set to 150W and the scanning speed was 90mm / s to construct a micro-nano rough surface with Ra of 1μm. The metal substrate was then plasma cleaned for 8 minutes. Argon was used as the working gas with a gas flow rate of 20L / min and a plasma power of 200W. The vacuum degree was maintained at 10Pa during the cleaning process.
[0027] (2) Coating material construction: Prepare a basic slurry containing 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and a polyvinyl alcohol solution with a balance of 5% by mass; the rare earths are yttrium oxide, lanthanum oxide, and cerium oxide, with a mass ratio of 5:3:2; during the preparation of the basic slurry, the temperature is controlled at 75°C, the dispersion time is 1 hour, and the dispersion speed is 550r / min; Gradient slurry: The alumina powder content in the base slurry is increased step by step by 1wt%; the zirconia powder and rare earth content are calculated according to the following relationship, and the contents of other powder components remain unchanged, among which the alumina powder, zirconia powder and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; among which the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z.
[0028] (3) Plasma spraying: The spraying distance was 100 mm and the angle was 80°. The base slurry was sprayed along the side of the metal substrate. The gradient slurry was sprayed every 40 μm of coating thickness. The content of alumina powder, zirconium oxide powder and rare earth in each gradient slurry sprayed was gradually increased based on the slurry of the previous layer. During the plasma spraying process, ultrasonic vibration was introduced to assist. The ultrasonic frequency was set to 30 kHz and the ultrasonic power was 250 W. The total spray thickness of the coating was 200 μm. The spraying gas was a mixture of argon and hydrogen, with an argon flow rate of 40 L / min, a hydrogen flow rate of 5 L / min and a plasma power of 450 W. After the first layer was sprayed, the temperature was raised to 1550 ° C in a vacuum state at a heating rate of 5 ° C / min and kept at this temperature for 30 minutes. After cooling to room temperature, the subsequent spraying was carried out. The subsequent sintering heating rate remained unchanged. The heating temperature increased by 5 ° C for each layer and the holding time remained unchanged.
[0029] (4) Thermal shock strengthening treatment: After plasma spraying, three thermal shocks were performed, with the temperature rising at 100°C / min and cooling at 60°C / min. The high temperature dwell time of each thermal shock was 10 minutes, and the low temperature dwell time was 6 minutes. Before the thermal shock strengthening treatment, the coating was vacuum annealed at 520°C, the holding time was 1 hour, and the vacuum degree was maintained at 1×10 -3 After the gradient coating is constructed, the coating surface is polished, and the surface roughness Ra after polishing is 0.5 μm.
[0030] Example 2 (1) Metal substrate pretreatment: Laser texturing technology was used to treat the metal substrate. The laser power was set to 225W and the scanning speed was set to 120mm / s to construct a micro-nano rough surface with Ra of 1.5μm. The metal substrate was then plasma cleaned for 9 minutes. Argon was used as the working gas with a gas flow rate of 25L / min and a plasma power of 250W. The vacuum degree was maintained at 13Pa during the cleaning process.
[0031] (2) Coating material construction: Prepare a basic slurry containing 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and a polyvinyl alcohol solution with a balance of 5% by mass; the rare earths are yttrium oxide, lanthanum oxide, and cerium oxide, with a mass ratio of 5:3:2; during the preparation of the basic slurry, the temperature is controlled at 75°C, the dispersion time is 1 hour, and the dispersion speed is 550r / min; Gradient slurry: The alumina powder content in the base slurry is increased step by step by 1wt%; the zirconia powder and rare earth content are calculated according to the following relationship, and the contents of other powder components remain unchanged, among which the alumina powder, zirconia powder and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; among which the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z.
[0032] (3) Plasma spraying: The spraying distance was 125 mm and the angle was 90°. The base slurry was sprayed along the side of the metal substrate. The gradient slurry was sprayed every 40 μm of coating thickness. The content of alumina powder, zirconium oxide powder and rare earth in each gradient slurry sprayed was gradually increased based on the slurry of the previous layer. During the plasma spraying process, ultrasonic vibration was introduced to assist. The ultrasonic frequency was set to 35 kHz and the ultrasonic power was 275 W. The total spray thickness of the coating was 200 μm. The spraying gas was a mixture of argon and hydrogen, with an argon flow rate of 45 L / min, a hydrogen flow rate of 6.5 L / min and a plasma power of 475 W. After the first layer was sprayed, the temperature was raised to 1550 ° C in a vacuum state at a heating rate of 5 ° C / min and kept at this temperature for 30 minutes. After cooling to room temperature, the subsequent spraying was carried out. The subsequent sintering heating rate remained unchanged. The heating temperature increased by 6.5 ° C for each layer and the holding time remained unchanged.
[0033] (4) Thermal shock strengthening treatment: After plasma spraying, three thermal shocks were performed, with a temperature increase of 110°C / min and a temperature decrease of 80°C / min. The high temperature dwell time of each thermal shock was 12.5 minutes, and the low temperature dwell time was 7 minutes. Before the thermal shock strengthening treatment, the coating was vacuum annealed at 560°C for 1.5 hours and the vacuum degree was maintained at 1.3×10 -3 After the gradient coating is constructed, the coating surface is polished, and the surface roughness Ra after polishing is 0.4 μm.
[0034] Example 3 (1) Metal substrate pretreatment: Laser texturing technology was used to treat the metal substrate. The laser power was set to 300W and the scanning speed was set to 150mm / s to construct a micro-nano rough surface with Ra2μm. The metal substrate was then plasma cleaned for 10 minutes. Argon was used as the working gas with a gas flow rate of 30L / min and a plasma power of 300W. The vacuum degree was maintained at 16Pa during the cleaning process.
[0035] (2) Coating material construction: Prepare a basic slurry containing 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and a polyvinyl alcohol solution with a balance of 5% by mass; the rare earths are yttrium oxide, lanthanum oxide, and cerium oxide, with a mass ratio of 5:3:2; during the preparation of the basic slurry, the temperature is controlled at 75°C, the dispersion time is 1 hour, and the dispersion speed is 550r / min; Gradient slurry: The alumina powder content in the base slurry is increased step by step by 1wt%; the zirconia powder and rare earth content are calculated according to the following relationship, and the contents of other powder components remain unchanged, among which the alumina powder, zirconia powder and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; among which the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z.
[0036] (3) Plasma spraying: The spraying distance is 150 mm and the angle is 100°. The base slurry is sprayed along the side of the metal substrate. The gradient slurry is sprayed every 40 μm of coating thickness. The content of alumina powder, zirconium oxide powder and rare earth in each gradient slurry sprayed is gradually increased based on the slurry of the previous layer. During the plasma spraying process, ultrasonic vibration assistance is introduced. The ultrasonic frequency is set to 40 kHz and the ultrasonic power is 300 W. The total spray thickness of the coating is 200 μm. The spraying gas is a mixture of argon and hydrogen, with an argon flow rate of 50 L / min, a hydrogen flow rate of 8 L / min, and a plasma power of 500 W. After the first layer is sprayed, the temperature is raised to 1550 ° C in a vacuum state at a heating rate of 5 ° C / min, and the temperature is kept at this temperature for 30 minutes. Then, after cooling to room temperature, the subsequent spraying is carried out. The subsequent sintering heating rate remains unchanged. The heating temperature increases by 8 ° C for each layer, and the holding time remains unchanged.
[0037] (4) Thermal shock strengthening treatment: After plasma spraying, four thermal shocks were performed, with a temperature increase of 120°C / min and a temperature decrease of 100°C / min. The high temperature dwell time of each thermal shock was 15 minutes, and the low temperature dwell time was 8 minutes. Before the thermal shock strengthening treatment, the coating was vacuum annealed at 600°C for 2 hours and the vacuum degree was maintained at 1.6×10 -3 After the gradient coating is constructed, the coating surface is polished, and the surface roughness Ra after polishing is 0.3 μm.
[0038] Example 4 (1) Metal substrate pretreatment: Laser texturing technology was used to treat the metal substrate. The laser power was set to 180W and the scanning speed was set to 100mm / s to construct a micro-nano rough surface with Ra of 1.2μm. The metal substrate was then plasma cleaned for 8.5min. Argon was used as the working gas with a gas flow rate of 22L / min and a plasma power of 220W. The vacuum degree was maintained at 11Pa during the cleaning process.
[0039] (2) Coating material construction: Prepare a basic slurry containing 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and a polyvinyl alcohol solution with a balance of 5% by mass; the rare earths are yttrium oxide, lanthanum oxide, and cerium oxide, with a mass ratio of 5:3:2; during the preparation of the basic slurry, the temperature is controlled at 75°C, the dispersion time is 1 hour, and the dispersion speed is 550r / min; Gradient slurry: The alumina powder content in the base slurry is increased step by step by 1wt%; the zirconia powder and rare earth content are calculated according to the following relationship, and the contents of other powder components remain unchanged, among which the alumina powder, zirconia powder and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; among which the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z.
[0040] (3) Plasma spraying: The spraying distance was 110 mm and the angle was 85°. The base slurry was sprayed along the side of the metal substrate. The gradient slurry was sprayed every 40 μm of coating thickness. The content of alumina powder, zirconium oxide powder and rare earth in each gradient slurry sprayed was gradually increased based on the slurry of the previous layer. During the plasma spraying process, ultrasonic vibration was introduced to assist. The ultrasonic frequency was set to 32 kHz and the ultrasonic power was 260 W. The total spray thickness of the coating was 200 μm. The spraying gas was a mixture of argon and hydrogen, with an argon flow rate of 42 L / min, a hydrogen flow rate of 5.5 L / min and a plasma power of 460 W. After the first layer was sprayed, the temperature was raised to 1550 ° C in a vacuum state at a heating rate of 5 ° C / min and kept at this temperature for 30 minutes. After cooling to room temperature, the subsequent spraying was carried out. The subsequent sintering heating rate remained unchanged. The heating temperature increased by 5.5 ° C for each layer and the holding time remained unchanged.
[0041] (4) Thermal shock strengthening treatment: After plasma spraying, four thermal shocks were performed, with a temperature increase of 105°C / min and a temperature decrease of 65°C / min. The high temperature dwell time of each thermal shock was 11 minutes, and the low temperature dwell time was 6.5 minutes. Before the thermal shock strengthening treatment, the coating was vacuum annealed at 530°C for 1.2 hours and the vacuum degree was maintained at 1.1×10 -3After the gradient coating is constructed, the coating surface is polished, and the surface roughness Ra after polishing is 0.45 μm.
[0042] Example 5 (1) Metal substrate pretreatment: Laser texturing technology was used to treat the metal substrate. The laser power was set to 270W and the scanning speed was set to 140mm / s to construct a micro-nano rough surface with Ra of 1.8μm. The metal substrate was then plasma cleaned for 9.5min. Argon was used as the working gas with a gas flow rate of 28L / min and a plasma power of 280W. The vacuum degree was maintained at 15Pa during the cleaning process.
[0043] (2) Coating material construction: Prepare a basic slurry containing 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and a polyvinyl alcohol solution with a balance of 5% by mass; the rare earths are yttrium oxide, lanthanum oxide, and cerium oxide, with a mass ratio of 5:3:2; during the preparation of the basic slurry, the temperature is controlled at 75°C, the dispersion time is 1 hour, and the dispersion speed is 550r / min; Gradient slurry: The alumina powder content in the base slurry is increased step by step by 1wt%; the zirconia powder and rare earth content are calculated according to the following relationship, and the contents of other powder components remain unchanged, among which the alumina powder, zirconia powder and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; among which the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z.
[0044] (3) Plasma spraying: The spraying distance was 140 mm and the angle was 95°. The base slurry was sprayed along the side of the metal substrate. The gradient slurry was sprayed every 40 μm of coating thickness. The content of alumina powder, zirconium oxide powder and rare earth in each gradient slurry sprayed was gradually increased based on the slurry of the previous layer. During the plasma spraying process, ultrasonic vibration was introduced to assist. The ultrasonic frequency was set to 38 kHz and the ultrasonic power was 290 W. The total spray thickness of the coating was 200 μm. The spraying gas was a mixture of argon and hydrogen, with an argon flow rate of 48 L / min, a hydrogen flow rate of 7.5 L / min and a plasma power of 490 W. After the first layer was sprayed, the temperature was raised to 1550 ° C in a vacuum state at a heating rate of 5 ° C / min and kept at this temperature for 30 minutes. After cooling to room temperature, the subsequent spraying was carried out. The subsequent sintering heating rate remained unchanged. The heating temperature increased by 7.5 ° C for each layer and the holding time remained unchanged.
[0045] (4) Thermal shock strengthening treatment: After plasma spraying, four thermal shocks were performed, with a temperature increase of 115°C / min and a temperature decrease of 90°C / min. The high temperature dwell time of each thermal shock was 14 minutes, and the low temperature dwell time was 7.5 minutes. Before the thermal shock strengthening treatment, the coating was vacuum annealed at 580°C for 1.8 hours and the vacuum degree was maintained at 1.5×10 -3 After the gradient coating is constructed, the coating surface is polished, and the surface roughness Ra after polishing is 0.35 μm.
[0046] Comparative Example 1 The difference from the technical solution of Example 1 is that no laser texturing treatment is performed.
[0047] Comparative Example 2 The difference from the technical solution of Example 1 is that ceramic phase gradient deposition is not achieved, and all spraying is performed using basic slurry.
[0048] Comparative Example 3 The difference from the technical solution of Example 1 is that no vacuum annealing treatment is performed.
[0049] Comparative Example 4 The difference from the technical solution of Example 1 is that no polishing process is performed.
[0050] test Coating bonding strength test Referring to GB / T8642-2002, "Determination of Tensile Bond Strength of Thermal Spray Coatings," the bond strength between the coating and the metal substrate was determined using a tensile test method. A cylindrical 304 stainless steel specimen was used as the metal substrate. The prepared coating specimens were bonded to a tensile fixture using a high-strength adhesive. A tensile load was applied at a rate of 1 mm / min on a universal testing machine until the coating separated from the substrate. The maximum tensile load was recorded, and the bond strength was calculated. Table 1
[0051] Table 1 shows that the coatings in the examples exhibit high bonding strength. This is because laser texturing creates a suitable micro-nano rough surface, enhancing the mechanical engagement between the substrate and the coating. Plasma cleaning removes contaminants and oxide layers from the substrate surface, increasing its surface activity and strengthening the adhesion between the coating and the substrate. Furthermore, the gradient-deposited ceramic phase and ultrasonic vibrations promote uniform spreading and refinement of the molten droplets, resulting in a tighter bond between the coating and the substrate.
[0052] Comparative Example 1 was not subjected to laser texturing treatment, and the surface roughness of the substrate was insufficient, resulting in a weakening of the mechanical bite between the coating and the substrate and a significant reduction in the bonding strength.
[0053] Comparative Example 2 did not achieve ceramic phase gradient deposition, and the stress distribution inside the coating was uneven, which easily led to stress concentration during the stretching process, thereby reducing the bonding strength.
[0054] Comparative Example 3 did not undergo vacuum annealing treatment, and the internal stress of the coating was relatively large. The internal stress was released during the stretching process, resulting in separation of the coating and the substrate, and a decrease in bonding strength.
[0055] Comparative Example 4 was not polished, which had little effect on the coating bonding strength.
[0056] Coating hardness test Test methods The coating hardness was measured using a Vickers hardness tester, referring to GB / T9797-2008, "Vickers Hardness Test for Thermally Sprayed Metals and Other Inorganic Coatings." Five different test points were selected on the coating surface, and a test force of 9.807 N was applied for 10 seconds. The diagonal length of the indentation was measured, and the Vickers hardness value was calculated.
[0057] Table 2
[0058] As can be seen in Table 2, the coatings in the examples exhibited high hardness. This is due to the gradient deposition of the ceramic phase, which gradually increases the hardness of the coating from the substrate to the surface, forming a hardness gradient. This structure effectively resists external loads and improves the coating's hardness. Furthermore, ultrasonic vibration facilitates the refinement and uniform spreading of the molten droplets, making the coating's structure denser and thus increasing its hardness. Furthermore, thermal shock treatment promotes the agglomeration and refinement of the ceramic phase particles, further increasing the coating's hardness.
[0059] Comparative Example 1 was not subjected to laser texturing treatment, which had no effect on the surface hardness of the coating.
[0060] Comparative Example 2 did not achieve ceramic phase gradient deposition, and the coating had an uneven organizational structure and uneven hardness distribution, thereby reducing the overall hardness.
[0061] Comparative Example 3 did not undergo vacuum annealing treatment, and the internal stress of the coating was relatively large. During the hardness test, the internal stress affected the formation of the indentation, resulting in a low measured hardness value.
[0062] Comparative Example 4 was not polished, and the coating surface was relatively rough, with many microcracks and defects, which would reduce the hardness of the coating.
[0063] Coating thermal shock performance test According to GB / T18684-2002 "Thermal shock test method for thermal spray coatings", 304 stainless steel was used as the metal substrate. The coating sample was heated to 800°C in a muffle furnace, kept at this temperature for 30 minutes, and then quickly placed in room temperature water to cool. This process was repeated until obvious cracks or peeling appeared on the coating. The number of thermal shocks was recorded. Table 3
[0064] Table 3 shows that the coatings in Example 1 exhibit excellent thermal shock resistance and exhibit a high number of thermal shock events. This is because the gradient-deposited ceramic phase effectively alleviates thermal stress in the coating during thermal cycling, reducing the initiation and propagation of cracks. Furthermore, vacuum annealing eliminates internal stress in the coating, and thermal shock hardening promotes the agglomeration and refinement of ceramic particles, making the coating's structure more stable and thus improving thermal shock resistance.
[0065] Comparative Example 1 was not subjected to laser texturing treatment, and the bonding strength between the substrate and the coating was poor. During the thermal cycle, the coating was easily peeled off from the substrate, resulting in a reduction in the number of thermal shocks.
[0066] Comparative Example 2 did not achieve ceramic phase gradient deposition, the thermal expansion coefficient of the coating did not match that of the substrate, and large thermal stress would be generated during the thermal cycle, resulting in cracking and peeling of the coating, and the number of thermal shocks was reduced.
[0067] Comparative Example 3 did not undergo vacuum annealing treatment, and the internal stress of the coating was relatively large. During the thermal cycle process, the internal stress and thermal stress were superimposed, which accelerated the destruction of the coating and reduced the number of thermal shocks.
[0068] Comparative Example 4 was not polished, and the coating surface was relatively rough, with many microcracks and defects. These defects would become crack sources during the thermal cycle process, resulting in a decrease in the number of thermal shocks.
[0069] In summary, the present invention's high-ceramic phase gradient coating preparation process achieves excellent adhesion between the coating and the substrate by optimizing various process parameters, improving the coating's hardness and thermal shock resistance. However, the comparative example exhibits poor coating performance due to the lack of some key processes or improper process parameter settings.
[0070] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. The preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification.
Claims
1. A process for preparing a high ceramic phase gradient coating, characterized in that: The following steps are involved: (1) Metal substrate pretreatment: The metal substrate is processed by laser texturing technology to construct a micro-nano rough surface with Ra1μm-2μm; (2) Coating material construction: The basic slurry includes: 12wt% silicon carbide powder, 20wt% zirconium oxide powder, 15wt% aluminum oxide powder, 3.5wt% boron nitride powder, 10wt% silicon dioxide powder, 0.45wt% rare earth, and the balance is 5wt% polyvinyl alcohol solution; Gradient slurry: The alumina powder content in the base slurry is gradually increased by 1wt%-1.5wt% to obtain; the zirconia powder and rare earth content are calculated according to the following relationship, and the content of other powder components remains unchanged, wherein the alumina powder, zirconia powder, and rare earth content satisfy the following formula: z=0.05x+0.01y-0.5; wherein the alumina powder content is x, the zirconia powder content is y, and the rare earth content is z; (3) Plasma spraying: Adjust the spraying distance to 100mm-150mm and the angle to 80°-100°, spray the base slurry along the side of the metal substrate, and then spray the gradient slurry every 40μm coating thickness. Each time the gradient slurry is sprayed, the content of alumina powder, zirconium oxide powder, and rare earth is gradually increased based on the slurry of the previous layer to achieve gradient deposition of the ceramic phase coating; After the first layer of base slurry is sprayed, sintering is carried out, and the temperature is raised to 1550℃ under vacuum at a heating rate of 5℃ / min, kept at this temperature for 30 minutes, and then cooled to room temperature before subsequent spraying. This cycle is repeated until all coatings are sprayed and sintered. Among them, the subsequent sintering heating rate remains unchanged, the heating temperature increases by 5-8℃ per layer, and the holding time remains unchanged; During the plasma spraying process, ultrasonic vibration assistance is introduced to promote the uniform spreading and refinement of the molten droplets through ultrasonic vibration; The total spray thickness of the coating is 200 μm; (4) Thermal shock strengthening treatment: After plasma spraying, perform 3-4 thermal shocks, heating at 100-120°C / min and cooling at 60-100°C / min, using thermal stress to promote the agglomeration and refinement of ceramic phase particles. Before thermal shock strengthening treatment, the coating is vacuum annealed at a temperature of 520°C-600°C for 1-2 hours to eliminate internal stress in the coating.
2. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: During the laser texturing process, the laser power is set to 150W-300W and the scanning speed is set to 90mm / s-150mm / s.
3. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: The rare earths selected are yttrium oxide, lanthanum oxide and cerium oxide, and the mass ratio of the three is 5:3:
2.
4. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: The ultrasonic frequency is set to 30kHz-40kHz, and the ultrasonic power is 250W-300W.
5. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: The vacuum degree of the vacuum annealing process was maintained at 1×10 -3 Pa-1.6×10 -3 Pa.
6. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: During the preparation of the basic slurry, the temperature is controlled at 75°C-80°C, the dispersion time is 1-2 hours, and the dispersion speed is 550r / min.
7. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: During plasma spraying, the spraying gas is a mixture of argon and hydrogen, and the plasma power is 450-500W; Among them, the argon flow rate in the mixed gas is 40L / min-50L / min, and the hydrogen flow rate is 5L / min-8L / min.
8. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: In the thermal shock strengthening treatment, the high temperature residence time of each thermal shock is 10min-15min, and the low temperature residence time is 6min-8min.
9. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: After the metal substrate is pretreated, the metal substrate is plasma cleaned. The plasma cleaning time is 8min-10min. Argon is used as the working gas for plasma cleaning. The gas flow rate is 20L / min-30L / min, the plasma power is 200W-300W, and the vacuum degree is maintained at 10Pa-16Pa during the cleaning process.
10. The process for preparing a high ceramic phase gradient coating according to claim 1, characterized in that: After the gradient coating is constructed, the coating surface is polished, and the surface roughness after polishing is Ra≤0.5μm.
Citation Information
Cited By
Multi-element oxide ceramic coating refractory brick material containing reinforcement phase and preparation method thereof
CN121470993A
Refractory brick material comprising a multi-oxide ceramic coating with reinforcing phase and method for its production
CN121470993B
Biphase hybrid anti-icing coating as well as preparation method and application thereof
CN121975431A